(3VeGfGJ GdeJge CKfGA eQMdI GdeMGceI aj GdfXGe GdSYhOj (B: s (3OQGSI ebGQfI (B/ s - (3UGdM YhV efUhQ GdLYjOs; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3HOCJ GdCYjf JQfh ef Ref djS HHYjO Edi JUhQ LOjO ddYOGdI GdLfGFjI jLeY aj WjGJg YfUQjf CSGSjf (B: (3GdJMhd ef GdYOGdI GdbgQjI Edi GdYOGdI GdQVGFjI ef LGfH (B: (3h GdESQGY aj GdELQGA GdLfGFj GdJbdjOj ef LGfH BNQ (B. (3JMhj GdELQGAGJ GdLfGFjI Hjf WjGJgG eaghejf CSGSjjf (B: (3GdChd OSJhQj bGFe Ydi CSS eYfhjI LhgQgG VQhQI MeGjI Mbhb GdEfSGf h MQjGJg (B: (3h GdBNQ eaghe Yedj jSJfO Ydi CSS faYjI bhGegG GdaGYdjI h GdSQYI dehGLgI MGSeI ddXGgQI GdELQGejI (B. (3h cdGgeG dg CgejJg h cjGfg (B: (3h cdGgeG jeKdGf eUdMI GLJeGYjI LOjQI HGdQYGjI h GdGYJHGQ(B. (3JfGhdJ GdTQjYI GdESdGejI GdZQGA(B: (3h cGf dgG aVd GdSHb ai JfGhd GdMQjI h Mbhb h VeGfGJ GdeJge efP eG jRjO Yf CQHYI YTQ bQfG(B: (3dchfgG JgOa Edi CSei GdZGjGJ h GdebGUO h eG ZGjI GdTQjYI GdSeMGA JbQjQ gPg GdVeGfGJ EdG GfWdGbG ef EjeGfgG HcQGeI GdEfSGf h HMbg ai eeGQSI Mbhbg h MQjGJg hUhdG Edi GdYOGdI GdefThOIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2015s
(3HHdjhLQGajG(B: (3UaMGJ (B467-489s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdeMGceI GdLfGFjIs; (3VeGfGJ GdeJges; (3bQjfI GdHQGAIs; (3GdGbfGY GdbVGFjs; (3GSJbdGd GdbVGAs; (3JbOjQ GdGOdIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs